Development of an improved parameter fitting method for planar biaxial testing using rakes. (31st January 2019) - Fehervary, Heleen; Vander Sloten, Jos; Famaey, Nele
Abstract: A correct estimation of the material parameters from a planar biaxial test is crucial since they will affect the outcome of the finite element model in which they are used. In a virtual planar biaxial experiment, a difference can be noticed in the stress calculated from the force measured experimentally at the rakes and the actual stress at the center of the sample. As a consequence, a classic parameter fitting does not result in a correct estimation of the material parameters. This difference is caused by the boundary conditions of the set‐up and is among others dependent on the sample material. To overcome this problem, a new parameter fitting procedure is proposed that takes this difference into account by calculating a finite element–based correction vector. This paper describes the methodology to apply this new parameter fitting procedure on real experimental data from a planar biaxial test using rakes. To this end, image processing is used to extract the experiment characteristics. This information is used to construct a finite element model. Two variations of the new parameter fitting procedure are investigated using two human aortic samples: a basic approach and an image‐based approach. The performance of the method is assessed by the difference between the force measured at the rakes during the experiment and the force at the rakes obtained from the finite element simulation. Both approaches of the new parameter fitting procedure lead to an improved estimation of the sample behavior compared with the classic approach. Abstract : This paper presents a new parameter fitting method for a rake‐based planar biaxial test that takes the boundary conditions of the experiment into account. To this end, an image‐based finite element model of the experiment is created to calculate a correction factor that can be applied to the experimental data. The new method results in a significant improvement of the parameter fitting results compared with the classic approach.